Transitive 7-Groups Degree 7N (N=2) - Hamidu, A. A. (NIU Journal of Humanities, 2023)
In this paper we successfully classify transitive 7-groups of degree 49 and other unique properties of these groups. Keywords: Abelian group, classification, degree, generator, isomorphism, p-groups, presentation, transitive.